In Vitro Digestion Patterns of Advanced Glycation End Products and α-Dicarbonyls in Biscuits and the Modulatory Effects of Ferulic Acid and Epicatechin - Xiaoxiang Peng; Huiyu Hu; Yuwei Liu; Jia Li; Yilun Huang; Haiwa Wang; Ziyi Wang; Yuting Wang (Foods)
The dietary intake amount of processing contaminants does not reflect their actual exposure risk due to interactions with the food matrix during gastrointestinal processes, which significantly modulate their bioaccessibility. This study systematically investigated the in vitro digestion patterns of advanced glycation end products (AGEs) and α-dicarbonyl compounds (α-DCs) in biscuits and the modulatory effects of ferulic acid and epicatechin. The results demonstrated that more than 80% of AGEs and α-DCs were present in the bioaccessible fraction of the samples after intestinal digestion. Ferulic acid (FA, 0.05%, w/w) significantly increased the AGEs content in the bioaccessible fraction after intestinal digestion compared to control samples. Conversely, FA at 0.2% and 0.5%, as well as epicatechin (EC) at 0.05%, significantly reduced the glyoxal and 3-deoxyglucosone levels during oral digestion and significantly increased these contaminants contents after gastric digestion. The higher the concentration of EC, the lower the level of methylglyoxal during oral and gastric digestion. In addition, we identified the adducts of FA with lysine and the adducts of EC with Nε-Carboxymethyl-lysine using LC-QTOF-MS, demonstrating the reactivity between polyphenols, amino acids and contaminants. This study provides guidance and suggestions for mitigating dietary exposure to AGEs and α-DCs.